Silicon-tin composite material, preparation method and application thereof, and battery

By using porous silicon material to coat the tin carbon layer and the chestnut-shaped carbon layer in lithium-ion batteries, and constructing graphene's silicon-tin composite material structure on the outer layer, the low first-effect and low silicon-based anode material in lithium-ion batteries are solved. Capacity retention problem achieves better electrochemical performance and cycling stability.

CN119297257APending Publication Date: 2025-01-10NINGBO SHANSHAN NEW MATERIAL TECH

Patent Information

Application Number
CN202411775794.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Due to the low first efficiency of silicon-based anode materials in lithium-ion batteries and low capacity retention rate under long cycles, existing carbon-coated nano-silicon materials still need to improve their electrochemical performance.

Method used

A silicon-tin composite material structure is adopted, wherein the core is porous silicon material, the first cladding layer is a tin-containing carbon layer, the second cladding layer is a chestnut-shaped carbon layer, and a graphene layer is constructed on the outer layer , prepared by solvent gel method and chemical bath deposition method.

Benefits of technology

It significantly improves the first-effect and cycling performance of lithium-ion batteries, enhances the electronic conductivity and lithium-ion diffusion rate, and ensures the high capacity retention and rate performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297257A_ABST
    Figure CN119297257A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-tin composite material, a preparation method and application thereof and a battery. The silicon-tin composite material sequentially comprises an inner core, a first coating layer and a second coating layer from inside to outside, the inner core comprises a silicon material, the first coating layer is a tin-containing carbon layer, and the second coating layer comprises a chestnut-shaped carbon layer; the first coating layer comprises a first carbon layer, tin dioxide nanoparticles and a second carbon layer, and the tin nanoparticles are located between the first carbon layer and the second carbon layer. The preparation method of the silicon-tin composite material comprises the following steps: S1, coating a tin-containing carbon layer on a silicon material by adopting a solvent gel method to obtain a first precursor; and S2, coating the first precursor with a second coating layer. The silicon-tin composite material disclosed by the invention has excellent conductivity and relatively low charge transfer internal resistance, and a battery assembled by the silicon-tin composite material has excellent capacity performance, cycle performance and coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-tin composite material and a preparation method, application and battery thereof. Background Art

[0002] Lithium-ion batteries underpin important applications ranging from portable electronics to electric vehicles and large-scale stationary energy storage. Its development is inextricably linked to the pursuit of high-performance active materials. High-capacity anode active materials are an essential component of next-generation high-energy-density lithium-ion batteries, and research directions are largely divided into metal anodes and silicon-based anodes. However, the volume expansion of silicon during lithiation means that the active materials need to be significantly optimized to enable reversible alloying / dealloying in repeated cycles without pulverizing or degrading the active materials. Modification methods of active materials, including structural regulation, interface engineering, binder design and optimization, and electrolyte composition control, have been widely studied to enhance the practical prospects of silicon-based anodes.

[0003] Patent application CN 118136819A introduces a carbon-coated nano-silicon negative electrode material and a preparation method thereof, wherein an organic carbon source, a silicon source, a dispersant and an organic solvent are mixed and dried to obtain a mixed powder; the mixed powder is heated to allow the organic carbon source and the silicon source to undergo an oxidation-reduction reaction to obtain a carbon-coated nano-silicon negative electrode material. The first efficiency of the obtained negative electrode material is only about 90% at a rate of 0.2C, and the capacity remains at 970mAh / g-1000 mAh / g after 100 cycles. The electrochemical performance of the carbon-coated nano-silicon negative electrode material needs to be improved. Therefore, it is necessary to further develop the capacity advantages of silicon-based materials and obtain negative electrode materials with excellent electrochemical performance. Summary of the invention

[0004] In order to alleviate the problems of low initial efficiency and low capacity retention rate of lithium-ion batteries in the prior art, the present invention proposes a silicon-tin composite material and its preparation method, application and battery. The silicon-tin composite material of the present invention has high electronic conductivity and lithium ion diffusion rate. The lithium-ion battery using the silicon-tin composite material as the negative electrode material has high initial efficiency and excellent cycle performance.

[0005] The present invention adopts the following technical solutions to solve the above technical problems:

[0006] The present invention provides a silicon-tin composite material, which comprises, from the inside to the outside, a core, a first coating layer and a second coating layer; the core comprises a silicon material, the first coating layer is a tin-containing carbon layer, and the second coating layer comprises a chestnut-shaped carbon layer; the first coating layer comprises a first carbon layer, tin dioxide nanoparticles and a second carbon layer, and the tin nanoparticles are located between the first carbon layer and the second carbon layer.

[0007] In the present invention, the silicon material may be a porous silicon material, such as a mesoporous silicon material.

[0008] In the present invention, preferably, the silicon material may be doped with heteroatoms, such as one or more of boron (B), phosphorus (P), nitrogen (N) and sulfur (S).

[0009] In some preferred embodiments of the present invention, the silicon material may be a porous silicon material doped with heteroatoms, such as a porous silicon material co-doped with B and P.

[0010] In the present invention, preferably, the second coating layer is doped with one or more of nitrogen, boron and phosphorus.

[0011] In the present invention, the silicon-tin composite material may further include a third coating layer, wherein the third coating layer is a graphene layer, and the third coating layer is coated on the outer surface of the second coating layer.

[0012] In the present invention, the silicon content in the silicon-tin composite material may be 54%-61%, where the percentage is the mass percentage of silicon element in the silicon-tin composite material.

[0013] In the present invention, the tin content in the silicon-tin composite material may be 6.0%-7.5%, where the percentage is the mass percentage of the tin element in the silicon-tin composite material.

[0014] In the present invention, the carbon content in the silicon-tin composite material may be 23%-31%, where the percentage is the mass percentage of carbon element in the silicon-tin composite material.

[0015] In the present invention, the nitrogen content in the silicon-tin composite material may be 0%-1.5%, where the percentage is the mass percentage of nitrogen in the silicon-tin composite material.

[0016] In the present invention, the boron content in the silicon-tin composite material may be 0%-1%, where the percentage is the mass percentage of the boron element in the silicon-tin composite material.

[0017] In the present invention, the phosphorus content in the silicon-tin composite material may be 0.7%-1.2%, where the percentage is the mass percentage of phosphorus element in the silicon-tin composite material.

[0018] In the present invention, the oxygen content in the silicon-tin composite material may be 7%-10%, where the percentage is the mass percentage of oxygen element in the silicon-tin composite material.

[0019] In the present invention, preferably, the silicon-tin composite material comprises, by mass percentage, 54%-61% silicon, 6.0%-7.5% tin, 23%-31% carbon, 0%-1.5% nitrogen, 0%-1% boron, 0.7%-1.2% phosphorus, and 7%-10% oxygen.

[0020] In the present invention, the pore size of the silicon-tin composite material may be 12-20 nm.

[0021] In the present invention, the electrical conductivity of the silicon-tin composite material can be (2.5-4.0)×10 4 S / m.

[0022] In the present invention, the charge transfer resistance of the silicon-tin composite material may be 13-25Ω.

[0023] The present invention provides a method for preparing a silicon-tin composite material, which comprises the following steps:

[0024] S1. Coating a tin-containing carbon layer on a silicon material using a solvent gel method, which includes the following steps:

[0025] S1-1, ultrasonically dispersing a surfactant and tin dioxide in water to form spherical micelles;

[0026] S1-2, adding a carbon source monomer, a nitrogen source and a catalyst, stirring to obtain a sol;

[0027] S1-3, adding silicon material to obtain a core-shell colloid;

[0028] S1-4, heating and polymerization to obtain a gel polymer-coated silicon material;

[0029] S1-5, carbonizing so that the gel polymer forms a tin-containing carbon layer to obtain a first precursor;

[0030] S2. Coating the first precursor with a chestnut-shaped carbon layer.

[0031] In the present invention, in step S1, the method for coating the tin-containing carbon layer can be conventional in the art, and preferably a sol-gel method is used.

[0032] In the present invention, in step S1, the silicon material may be a conventional silicon material in the art. Preferably, the silicon material is a porous silicon material. Preferably, the silicon material is a silicon material doped with heteroatoms, wherein, preferably, the heteroatoms are boron (B) and / or phosphorus (P). More preferably, the silicon material is a porous silicon material doped with heteroatoms, for example, a porous silicon material co-doped with B and P.

[0033] In the present invention, preferably, the molar ratio of the surfactant to the tin dioxide in step S1-1 is (0.2-0.55):(0.8-1.5), preferably (0.246-0.55):(0.8-1.5).

[0034] Preferably, the tin dioxide in step S1-1 is porous tin dioxide. More preferably, the tin dioxide is porous tin dioxide with a gel structure.

[0035] Preferably, the surfactant in step S1-1 is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.

[0036] Preferably, the nitrogen source in step S1-2 is one or more of p-nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile).

[0037] Preferably, the catalyst in step S1-2 is a base compound.

[0038] Wherein, the alkaline compound can be one or more of sodium carbonate, sodium hydroxide and sodium citrate.

[0039] Preferably, the carbon source monomers in step S1-2 are resorcinol and / or formaldehyde. More preferably, the carbon source monomers in step S1-2 can be resorcinol and formaldehyde, and the molar ratio of resorcinol to formaldehyde is preferably (1-3): (1-3).

[0040] Preferably, the molar ratio of the carbon source monomer, nitrogen source and catalyst in step S1-2 to the surfactant in step S1-1 is (1.0-3.0): (0.01-0.09): (0.007-0.03): (0.2-0.55).

[0041] Preferably, the molar ratio of the silicon material added in step S1-3 to the catalyst in step S1-2 is (1.5-2.5): (0.007-0.03).

[0042] Preferably, the polymerization temperature in step S1-4 is 80-100°C, preferably 85-100°C.

[0043] Preferably, the polymerization time in step S1-4 is 2-6 hours.

[0044] Preferably, the gel polymer-coated silicon material in step S1-4 is a tin-carbon co-encapsulated silicon material.

[0045] Preferably, the carbonization temperature in step S1-5 is 550-850°C.

[0046] Preferably, the carbonization time in step S1-5 is 2-6 hours.

[0047] Preferably, the carbonization in step S1-5 further includes rinsing and drying, wherein preferably, water and / or ethanol may be used for rinsing.

[0048] In the present invention, preferably, step S1-0: preparation of porous tin dioxide is further included before step S1-1.

[0049] Preferably, the preparation method of the porous tin dioxide in step S1-0 comprises: adding an alkali solution dropwise to an inorganic tin source solution until the pH value of the solution is higher than 5.0, stirring and mixing, filtering, washing, and drying to obtain porous tin dioxide. Preferably, the inorganic tin source can be one or more of anhydrous tin chloride, stannous chloride, and stannous sulfate.

[0050] In some preferred embodiments of the present invention, in step S2, the first precursor is coated with a chestnut-shaped carbon layer by a chemical bath deposition method, comprising the following steps:

[0051] S2-1, ultrasonically dispersing the first precursor in a quaternary ammonium salt aqueous solution to obtain a first precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the first precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A;

[0052] S2-2, heat-treating the composite material A to obtain a composite material B;

[0053] S2-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source monomer and an initiator, reacting under stirring, centrifuging, washing, and drying to obtain a composite material C;

[0054] S2-4, calcining the composite material C, and cooling to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer;

[0055] S2-5. Treat the composite material D with acid to remove the nickel layer, wash, and dry to form a chestnut-shaped carbon layer.

[0056] In the present invention, the quaternary ammonium salt in step S2-1 may be one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.

[0057] Preferably, in step S2-1, the mass ratio of the first precursor to the quaternary ammonium salt is (0.1-0.5): (0.009-0.05).

[0058] Preferably, the nickel salt in step S2-1 is nickel acetate, nickel nitrate or nickel sulfate.

[0059] Preferably, the initiator in step S2-1 may be one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate.

[0060] Preferably, the mass ratio of the nickel salt, the initiator and the first precursor in step S2-1 is (0.1-0.5): (0.02-0.1): (0.1-0.5).

[0061] Preferably, the stirring in step S2-1 is performed in an oil bath at 25°C.

[0062] Preferably, the centrifugation time in step S2-1 is 10-30 min, for example 20 min.

[0063] Preferably, the centrifugal speed in step S2-1 is 200-300 r / min, for example 250 r / min.

[0064] Preferably, the temperature of the heat treatment in step S2-2 is 350-600°C.

[0065] Preferably, the constant temperature time of the heat treatment in step S2-2 is 2-5 hours.

[0066] Preferably, the heating rate of the heat treatment in step S2-2 is 1-10°C / min.

[0067] The heating rate refers to the heating rate during the process of heating to the heat treatment temperature.

[0068] In the present invention, the surfactant in step S2-3 may be an anionic surfactant.

[0069] Preferably, the anionic surfactant may be one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate.

[0070] Preferably, the initiator in step S2-3 is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate.

[0071] Preferably, the mass ratio of the surfactant, carbon source monomer and initiator in step S2-3 is (3-10): (0.1-0.3): (0.2-0.6).

[0072] Preferably, the carbon source monomer in step S2-3 is pyrrole and / or pyridine.

[0073] Preferably, the calcination temperature in step S2-4 is 650-850°C.

[0074] Preferably, the calcination time in step S2-4 is 3-6 hours.

[0075] Preferably, the calcination in step S2-4 is performed in an inert atmosphere. Preferably, the inert atmosphere can be high-purity nitrogen, helium, neon or argon.

[0076] Preferably, the cooling rate of the cooling in step S2-4 is 10-20°C / min, for example 15°C / min.

[0077] Preferably, the acid used in the acid treatment in step S2-5 is one or more of hydrochloric acid, sulfuric acid and nitric acid.

[0078] Preferably, the concentration of the acid in step S2-5 is 0.05-0.2 mol / L.

[0079] Preferably, the drying temperature in step S2-5 is 60-80°C.

[0080] Preferably, the drying time in step S2-5 is 6-24 hours.

[0081] In the present invention, the product obtained in step S2 is recorded as the second precursor. Preferably, step S2 further includes: S3, coating the second precursor with a graphene layer.

[0082] The coated graphene layer may be formed by a coating method conventionally used in the art. Preferably, coating the second precursor with a graphene layer comprises the following steps:

[0083] S3-1, adding the second precursor and humic acid into water to obtain a premix, and adding an ammonia solution under stirring;

[0084] S3-2, heating, sintering treatment, cooling;

[0085] S3-3, carbonization, graphene layer is formed in situ after thermal decomposition of humic acid.

[0086] In the present invention, preferably, in step S3-1, the humic acid is humic acid powder.

[0087] Preferably, in step S3-1, the mass ratio of the second precursor to the humic acid is (6-15):1.

[0088] Preferably, in step S3-1, the solid-liquid ratio of the premix is ​​1:(10-15), for example, 1:10.

[0089] Preferably, in step S3-1, the mass concentration of the aqueous ammonia solution is 22-32%, for example, 28%.

[0090] Preferably, in step S3-1, the amount of the aqueous ammonia solution used allows the humic acid to be completely dissolved.

[0091] Preferably, in step S3-1, the ammonia solution is added dropwise. Preferably, the rate of the dropwise addition is 100-180 mL / min.

[0092] Preferably, in step S3-2, the heating temperature is 80-100°C, for example, 90°C.

[0093] Preferably, in step S3-2, the sintering temperature is 200-300°C, for example, 280°C.

[0094] Preferably, in step S3-2, the sintering time is 1-3 h, for example, 2 h.

[0095] Preferably, in step S3-2, the sintering is performed in a microwave oven.

[0096] Preferably, in step S3-3, the carbonization temperature is 500-850° C., for example, 800° C. Preferably, the heating rate to the carbonization temperature is 1-10° C. / min, for example, 3° C. / min.

[0097] Preferably, in step S3-3, the carbonization time is 8-15 h, for example, 10 h.

[0098] Preferably, in step S3-3, the carbonization is carried out in a tubular furnace.

[0099] Preferably, in step S3-3, the carbonization is performed in an inert atmosphere. Preferably, the inert atmosphere can be selected from one or more of nitrogen, helium, neon and argon. More preferably, the nitrogen is high-purity nitrogen.

[0100] In the present invention, before step S1, the following step may be further included: S0, preparing a porous silicon material. Preferably, the porous silicon material is prepared by a sol-gel method and a magnesium thermal reduction method.

[0101] In some preferred embodiments of the present invention, in step S1, the silicon material may be a porous silicon material co-doped with B and P, and the preparation method thereof comprises the following steps:

[0102] S0-1, stirring a mixture containing a silicon source, a catalyst, a quaternary ammonium salt, a phosphorus source and a boron source, ultrasonically dispersing the mixture and centrifugally collecting the mixture, and calcining the mixture to obtain mesoporous silica;

[0103] S0-2, calcining the mixture of the mesoporous silica, magnesium powder and halogen metal compound to obtain a porous silicon material precursor;

[0104] S0-3, etching the porous silicon material precursor in an acid aqueous solution to obtain a B and P co-doped porous silicon material.

[0105] In the present invention, preferably, the mass ratio of the silicon source, catalyst, quaternary ammonium salt, phosphorus source and boron source in step S0-1 is (3-7.2): (7-13): (1-2.5) (0.3-0.8): (0.1-0.2).

[0106] Preferably, the silicon source in step S0-1 is one or more of ethyl orthosilicate, methyl silane orthosilicate and silicate, wherein the silicate is one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.

[0107] Preferably, the catalyst in step S0-1 is concentrated ammonia water, wherein the concentration of the concentrated ammonia water is preferably 28 wt%.

[0108] Preferably, the phosphorus source in step S0-1 is one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate.

[0109] Preferably, the boron source in step S0-1 is one or more of boric acid, triethyl borate and tripropyl borate.

[0110] Preferably, the quaternary ammonium salt in step S0-1 is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.

[0111] Preferably, the ultrasonic dispersion time in step S0-1 is 30-50 min.

[0112] Preferably, the stirring in step S0-1 is performed in an oil bath at 35°C.

[0113] Preferably, the stirring time in step S0-1 is 8-12 hours.

[0114] Preferably, the calcination temperature in step S0-1 is 500-750°C.

[0115] Preferably, the heating rate of the calcination in step S0-1 is 1-10°C / min.

[0116] Preferably, the calcination time in step S0-1 is 3-12 hours.

[0117] Preferably, the calcination in step S0-1 is carried out under an inert atmosphere.

[0118] Preferably, the inert atmosphere in step S0-1 is one or more of argon, helium and neon.

[0119] In the present invention, preferably, the halogen metal compound in step S0-2 is one or more of sodium chloride, sodium bromide and potassium chloride.

[0120] Preferably, the mass ratio of the mesoporous silica, magnesium powder and halogen metal compound in step S0-2 is 1:(0.85-1):(3-7).

[0121] Preferably, the calcination temperature in step S0-2 is 500-800°C.

[0122] Preferably, the heating rate of the calcination in step S0-2 is 1-10°C / min.

[0123] Preferably, the calcination time in step S0-2 is 3-12 hours.

[0124] Preferably, the calcination in step S0-2 is carried out under an inert atmosphere.

[0125] Preferably, the inert atmosphere in step S0-2 is one or more of argon, helium and neon.

[0126] In the present invention, preferably, the acid in the acid aqueous solution in step S0-3 is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid and oxalic acid.

[0127] Preferably, the concentration of the acid aqueous solution in step S0-3 is 2-6 mol / L, for example 2 mol / L.

[0128] Preferably, the etching time in step S0-3 is 3-5 hours.

[0129] In the present invention, the drying method involved in each step is independently any one of the following ①-③:

[0130] ① Freeze drying, preferably, the drying temperature is -30-(-80)°C; preferably, the drying time is 3-7h;

[0131] ②CO2 supercritical drying, preferably, the drying temperature is 10-40°C; preferably, the drying pressure is 10-15kPa; preferably, the drying time is 1-3h;

[0132] ③ Vacuum drying, preferably, the drying temperature is 60-90°C; preferably, the drying time is 6-24h.

[0133] The invention provides a silicon-tin composite material prepared by adopting the preparation method of the silicon-tin composite material.

[0134] The present invention provides an application of the silicon-tin composite material as described above as an electrode material in a battery.

[0135] Wherein, the electrode material is preferably a negative electrode material.

[0136] The present invention also provides a battery, which comprises the silicon-tin composite material.

[0137] In the present invention, the battery is preferably a lithium ion battery.

[0138] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0139] The reagents and raw materials used in the present invention are commercially available.

[0140] The positive and progressive effects of the present invention are:

[0141] (1) The problem of volume expansion of silicon materials is alleviated by multi-layer carbon coating. Tin-carbon co-coating is used in the layer close to the silicon material, and graphene is further coated on the carbon layer far from the silicon material, which reduces the impact of the low-capacity carbon layer on the material capacity. At the same time, the introduction of tin improves the electronic conductivity of the silicon material and enhances its lithium ion diffusion rate.

[0142] (2) By constructing a chestnut-shaped carbon layer, the current density is made more uniform and the lithium ion transfer rate is increased, thereby simultaneously enhancing the battery's rate performance and cycle stability.

[0143] (3) In the preferred technical solution, a graphene layer is also provided on the outermost layer of the material. The introduction of graphene further improves the electronic conductivity and lithium ion diffusion rate of the silicon material. The graphene layer and the chestnut-shaped carbon layer construct an outer three-dimensional porous structure. The coordinated effect of the two further makes the current density more uniform and the lithium ion transmission rate faster, further optimizing the rate performance and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0144] Figure 1 This is a schematic diagram of the structure of the silicon-tin composite material prepared in Example 1 of the present invention; wherein:

[0145] 1 is the core, 11 is the silicon material, 12 is the silicon pore, 13 is the B element, and 14 is the P element;

[0146] 2 is a first coating layer, 21 is a first carbon layer, 22 is a void, 23 is tin dioxide nanoparticles, and 24 is a second carbon layer;

[0147] 3 is the second coating layer, 31 is a gap, and 32 is a chestnut-shaped structure;

[0148] 4 is a graphene layer.

[0149] Figure 2 Schematic diagram of the cycle performance of the graphene-coated silicon-tin composite material prepared in Example 1 of the present invention.

[0150] Figure 3 Schematic diagram of the rate performance of the graphene-coated silicon-tin composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0151] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0152] Hexadecyltrimethylammonium bromide, analytical grade, was purchased from Wanhua Chemical Co., Ltd.;

[0153] The nitrogen source (pyridine) was purchased from Wanhua Chemical Co., Ltd.;

[0154] Resorcinol and formaldehyde were of analytical grade and purchased from Sinopharm Group;

[0155] Hydrochloric acid, analytical grade, was purchased from Sinopharm Group;

[0156] Sodium carbonate, analytical grade, was purchased from Wanhua Chemical Co., Ltd.;

[0157] Quaternary ammonium salt (alkyl dimethyl benzyl ammonium bromide), analytical grade, was purchased from Hangzhou Jessica Chemical Co., Ltd.;

[0158] Nickel acetate, analytical grade, was purchased from Sinopharm Group;

[0159] Potassium persulfate, analytical grade, was purchased from Wanhua Chemical Co., Ltd.;

[0160] Pyridine and pyrrole of analytical grade were purchased from Wanhua Chemical Co., Ltd.

[0161] Example 1

[0162] S0: Preparation of porous silicon materials

[0163] S0-1, dissolve hexadecyltrimethylammonium bromide, triethyl borate and phytic acid in 250 mL of ethanol aqueous solution (volume ratio of ethanol to water is 1:4) in a mass ratio of 1.5:0.5:0.12, stir for 45 minutes, and then ultrasonically treat for 45 minutes. Then, add 10 mL of concentrated ammonia (28 wt%). Then add 5.6 mL of ethyl orthosilicate to the mixed solution, and stir the mixed solution in an oil bath at 35°C for 10 hours. Finally, collect the product by centrifugation and wash it alternately with water and ethanol for 5 times. The final product was calcined in a tubular furnace at 600°C for 6.5 hours at a heating rate of 3°C / min and nitrogen conditions to prepare mesoporous silica;

[0164] S0-2, mesoporous silica was mixed with magnesium powder and sodium chloride in a mass ratio of 1:0.85:5. Magnesium thermal reduction was carried out in nitrogen with a heating rate of 1°C / min and calcined at 650°C for 5h;

[0165] S0-3. Treat the calcined mixture in 250 mL of 2 mol / l hydrochloric acid for 4 h, filter and dry to obtain a B and P co-doped porous silicon material.

[0166] S1: Coated with tin-containing carbon layer

[0167] S1-0, mix 78mmol of anhydrous tin chloride with 135mL of deionized water, stir until completely dissolved, and stir the mixture for 20 minutes to ensure complete dissolution of the anhydrous tin chloride. After sufficient stirring, drop 67.5mL of 2mol / L sodium carbonate solution into the reaction mixture, and the reaction is continued for 30min under N2 atmosphere. When the pH value of the solution reaches above 5.0, a white precipitate is formed. Filter the obtained precipitate and rinse it repeatedly with water and ethanol respectively. Then dry it under vacuum at 80℃ overnight to obtain porous tin dioxide;

[0168] S1-1, 0.35 mmol of hexadecyltrimethylammonium bromide and 1.2 mmol of porous tin dioxide are ultrasonically dispersed in 5.6 mol of deionized water to form spherical micelles, and the porous tin dioxide powder is fixed on the spherical micelles;

[0169] S1-2, adding a mixture of 0.02 mmol pyrrole, 0.9 mmol resorcinol, 0.9 mol formaldehyde and 0.01 mmol sodium carbonate, and continuously stirring to obtain a surface-stabilized sol;

[0170] S1-3, adding 1.8 mmol of silicon material to obtain a surfactant-stabilized core-shell colloid;

[0171] S1-4, polymerizing the core-shell colloid at 85° C. for 3 h, and obtaining a gel polymer-coated silicon material after drying;

[0172] S1-5. Heat treatment was performed at 650°C for 3 h under nitrogen conditions, followed by repeated rinsing with water and ethanol, and vacuum drying at 80°C for 10 h to form a tin-containing carbon layer.

[0173] S2: Chestnut-shaped carbon layer

[0174] S2-1. Add 0.1g of the first precursor to 50 mL of deionized water dissolved with 0.01g of hexadecyltrimethylammonium bromide, stir, and ultrasonically treat for 45 minutes to ensure that the first precursor is well distributed and preserved. Dissolve 0.1g of nickel acetate and 0.02g of sodium persulfate in 50 mL of distilled water. After complete dissolution, slowly add to the first precursor dispersion. After stirring for 45 minutes, add 20 mL of 1.5mol / l low-concentration ammonia water. Stir again at 25°C in an oil bath, and finally, collect the product by centrifugation (250r / min, 25min), and vacuum dry at 85°C for 10 hours to obtain composite material A;

[0175] S2-2, heating the nanoparticles of composite material A at a rate of 3°C / min under argon and maintaining the temperature at 450°C for 4 hours to obtain composite material B;

[0176] S2-3. Dissolve 8 mg of sodium dodecyl sulfate in 250 mL of deionized water. Add 0.1 g of composite material B and stir for 45 min. Then add 0.2 mL of pyrrole and stir in an ice bath at 3°C ​​for 45 min. At the same time, dissolve 0.34 g of sodium persulfate in 40 mL of distilled water. After complete dissolution, add it to the pyrrole mixed solution and stir for 24 h at a reaction temperature below 5°C. At the end of the reaction, collect the product by centrifugation, wash with distilled water and ethanol in turn to remove impurities, and vacuum dry at 85°C for 12 h to obtain composite material C;

[0177] S2-4, calcining the composite material C at 750° C. for 5 h in an argon atmosphere, and obtaining a composite material D coated with a nitrogen-doped carbon layer after cooling;

[0178] S2-5, remove nickel monoxide in composite material D with 200 mL of 5 mol / l hydrochloric acid, wash the material with deionized water to neutrality, and finally dry it under vacuum at 85° C. for 12 h. The obtained product is recorded as the second precursor.

[0179] S3: Graphene coating

[0180] S3-1, adding the second precursor and humic acid powder into deionized water at a mass ratio of 10:1 and mixing evenly, controlling the solid-liquid ratio at 1:10, and adding a 28wt% ammonia solution dropwise while stirring until the humic acid powder is completely dissolved;

[0181] S3-2, heating to 90°C and maintaining the temperature until the solvent is evaporated, so that the humic acid is evenly coated on the surface of the second precursor to obtain the humic acid-coated second precursor; the humic acid-coated second precursor is placed in a microwave oven at a temperature of 280°C for 2 hours, cooled and taken out, and then placed in a tube furnace, heated to 800°C at a rate of 3°C / min in an inert atmosphere and maintained for 10 hours, and cooled to obtain a silicon-tin composite material (the structural schematic diagram of the silicon-tin composite material is shown in FIG. Figure 1 as shown).

[0182] Example 2

[0183] The difference from Example 1 is that the boron source in step S0-1 is replaced by boric acid, and the other steps are under the same conditions as in Example 1.

[0184] Example 3

[0185] The difference from Example 1 is that the phosphorus source in step S0-1 is replaced by diammonium hydrogen phosphate, and the other steps are the same as the conditions in Example 1.

[0186] Example 4

[0187] The difference from Example 1 is that the quaternary ammonium salt in step S2-1 is replaced by octadecyltrimethylammonium chloride, and the other steps are the same as those in Example 1.

[0188] Example 5

[0189] The difference from Example 1 is that the calcination temperature in step S0-2 is 600° C., and the conditions of other steps are the same as those in Example 1.

[0190] Example 6

[0191] The difference from Example 1 is that the inorganic tin source in step S1-0 is replaced by stannous sulfate, and the other steps are the same as those in Example 1.

[0192] Example 7

[0193] The difference from Example 1 is that the surfactant in step S1-1 is replaced by alkyl dimethyl benzyl ammonium bromide, and the other steps are under the same conditions as in Example 1.

[0194] Example 8

[0195] The difference from Example 1 is that the nitrogen source in step S1-2 is replaced by melamine, and the other steps are under the same conditions as in Example 1.

[0196] Example 9

[0197] The difference from Example 1 is that the alkaline solution in step S1-2 is replaced by sodium hydroxide solution, and the other steps are the same as the conditions in Example 1.

[0198] Example 10

[0199] The difference from Example 1 is that the molar ratio of resorcinol to formaldehyde in step S1-2 is 1:800, and the other steps are under the same conditions as in Example 1.

[0200] Embodiment 11

[0201] The difference from Example 1 is that 1.5 mmol of silicon material is added in step S1-3, and the other steps are under the same conditions as in Example 1.

[0202] Example 12

[0203] The difference from Example 1 is that the heat treatment temperature in step S1-5 is 600°C, and the conditions of other steps are the same as those in Example 1.

[0204] Embodiment 13

[0205] The difference from Example 1 is that the drying method in step S2-1 is CO2 supercritical drying, the temperature is 20°C, the pressure is 10 kPa, and the drying time is 1.5 h. The other steps are the same as the conditions in Example 1.

[0206] Embodiment 14

[0207] The difference from Example 1 is that 0.15 g of the first precursor is added in step S2-1, and the other steps are under the same conditions as in Example 1.

[0208] Embodiment 15

[0209] The difference from Example 1 is that 0.12 g of nickel acetate and 0.02 g of sodium persulfate are added in step S2-1, and the other steps are the same as those in Example 1.

[0210] Example 16

[0211] The difference from Example 1 is that pyrrole in step S2-3 is replaced by pyridine, and the other steps are under the same conditions as in Example 1.

[0212] Embodiment 17

[0213] The difference from Example 1 is that the calcination temperature in step S2-4 is 700°C, and the conditions of other steps are the same as those in Example 1.

[0214] Embodiment 18

[0215] The difference from Example 1 is that in step S3-1, the mass ratio of the second precursor to the humic acid powder is 10:1.5, and the other steps are the same as those in Example 1.

[0216] Embodiment 19

[0217] The difference from Example 1 is that the solid-liquid ratio in step S3-1 is controlled at 1:12, and the other steps are under the same conditions as in Example 1.

[0218] Embodiment 20

[0219] The difference from Example 1 is that the calcination temperature in step S3-2 is 750°C, and the conditions of other steps are the same as those in Example 1.

[0220] Embodiment 21

[0221] The difference from Example 1 is that ordinary silicon is directly used for doping in step S0-2, and the conditions of other steps are the same as those of Example 1.

[0222] Embodiment 22

[0223] The difference from Example 1 is that steps S0-2 and S0-3 are not performed, that is, the mesoporous silicon spheres are not doped with boron and phosphorus, and the other steps are under the same conditions as in Example 1.

[0224] Embodiment 23

[0225] The difference from Example 1 is that step S3 is not performed, that is, graphene layer coating is not performed, and the other steps are under the same conditions as in Example 1.

[0226] Comparative Example 1:

[0227] The difference from Example 1 is that it is pure silicon powder.

[0228] Comparative Example 2:

[0229] The difference from Example 1 is that the tin dioxide powder is pure.

[0230] Comparative Example 3:

[0231] The difference from Example 1 is that only step S0 is performed, that is, the porous silicon material is co-doped with B and P.

[0232] Comparative Example 4:

[0233] The difference from Example 1 is that in step S3-1, the mass ratio of the second precursor to the humic acid powder is 1:1, and the other steps are the same as those in Example 1.

[0234] Comparative Example 5:

[0235] The difference from Example 1 is that the polymerization temperature in step S1-4 is 150° C., and the conditions of other steps are the same as those in Example 1.

[0236] Comparative Example 6:

[0237] The difference from Example 1 is that only step S0 and step S1 are performed, that is, only the first coating layer is provided, and the other steps are under the same conditions as in Example 1.

[0238] Comparative Example 7

[0239] The difference from Example 1 is that in step S1-1, ordinary tin dioxide is used to replace porous tin dioxide, and the other steps are under the same conditions as in Example 1.

[0240] Comparative Example 8

[0241] The difference from Example 1 is that tin dioxide is not added in step S1, and the other steps are under the same conditions as in Example 1.

[0242] Physical and chemical properties test:

[0243] After XRF testing, the element content in the composite material synthesized by the present invention was tested by microwave digestion method. The embodiment was pre-treated by mixing 2±0.05g of stearic acid and 6±0.5g of the sample to be tested, grinding them, pressing them into tablets, and then TM The test was conducted in 200 equipment; the test conditions: the air pressure was greater than 2MPa. The conductivity was measured using the OrionStar TM The conductivity is measured by A212 benchtop meter at room temperature. The pore size is measured by POROLUX Cito instrument; the electrode rebound is measured in an 80℃ oven or in a room temperature oven. The internal resistance is measured by electrochemical impedance spectroscopy (compacted density 1.65g / cm 3 ) were obtained, and the above physical and chemical properties test results are shown in Table 1.

[0244] Table 1

[0245] Material Silicon content% Tin content% Carbon content% Oxygen content% Phosphorus content% Boron content% D50 / nm Conductivity (×10^4 S / m) Aperture nm Charge transfer resistance Ω Example 1 58.8 7.02 24.9 8.24 0.81 0.12 155 3.296 12.8 14.8 Example 2 56.1 6.12 28.7 7.98 0.73 0.16 150 3.434 13.7 15.8 Example 3 57.8 7.32 25.5 8.34 0.81 0.12 155 3.721 12.8 14.8 Example 4 59.2 6.68 23.9 9.12 0.67 0.23 145 3.691 16.7 17.1 Example 5 54.3 6.29 30.5 7.65 0.91 0.21 155 3.656 15.3 16.2 Example 6 57.3 7.21 25.4 8.56 1.01 0.26 165 3.684 14.9 17.8 Example 7 56.4 6.79 27.3 8.35 0.89 0.17 140 3.583 12.5 16.7 Example 8 58.3 6.34 26.3 7.89 0.93 0.12 135 3.476 15.1 16.8 Example 9 57.5 7.25 26.4 7.68 0.95 0.17 165 3.621 17.4 16.4 Example 10 58.7 6.87 25.8 7.48 0.79 0.16 160 3.708 12.8 15.7 Embodiment 11 59.9 6.91 24.5 7.39 0.88 0.26 156 3.682 16.2 15.1 Example 12 60.3 6.35 23.8 8.12 0.96 0.23 155 3.675 12.7 17.9 Embodiment 13 54.9 6.71 28.7 8.32 0.87 0.21 145 3.618 13.7 18.2 Embodiment 14 58.2 7.11 24.3 9.18 0.78 0.19 165 3.547 13.9 16.5 Embodiment 15 55.4 7.18 28.6 7.64 0.75 0.26 162 3.672 12.8 15.3 Example 16 56.8 6.82 28.2 7.09 0.84 0.15 147 3.375 17.2 13.9 Embodiment 17 57.3 6.52 25.7 9.38 0.93 0.12 149 3.389 15.3 18.3 Embodiment 18 59.4 7.35 24.6 7.29 0.99 0.23 153 3.432 14.6 16.9 Embodiment 19 58.2 6.71 25.7 8.17 1.04 0.17 162 3.649 16.3 13.6 Embodiment 20 54.3 6.19 30.2 7.45 0.89 0.18 155 3.281 16.8 13.8 Embodiment 21 57.3 7.32 25.8 8.16 1.12 0.18 146 2.754 18.7 20.7 Embodiment 22 56.8 6.78 28.5 7.56 / / 158 2.987 19.2 22.9 Embodiment 23 60.7 7.43 20.9 9.12 0.98 0.21 153 3.721 14.7 24.9 Comparative Example 1 100 / / / / 70 / 1.1 273 Comparative Example 2 / 78.66 / 21.34 / / 65 3.218 12.5 128 Comparative Example 3 96.85 / / 0.98 0.89 1.12 75 1.129 12.6 187 Comparative Example 4 32.32 3.86 52.09 11.05 0.23 0.01 120 1.641 15.8 23.4 Comparative Example 5 56.15 6.29 24.65 7.81 0.77 0.12 158 2.996 15.2 76.3 Comparative Example 6 65.81 11.48 16.34 5.36 0.68 0.85 95 2.417 16.2 56.1 Comparative Example 7 60.81 11.48 20.7 5.36 0.68 0.85 95 2.491 16.2 56.1 Comparative Example 8 66.5 0 31.2 1.12 0.71 0.12 145 8.174 17.5 32.8

[0246] Button lithium-ion battery test:

[0247] The preparation method of the button cell used for testing the electrochemical performance is as follows: 95.5 g of the battery negative electrode material prepared in the embodiment and the comparative example are mixed evenly with 1.5 g of the conductive agent (KS-6), 1.5 g of CMC, and 1.5 g of SBR, and coated on a copper foil (thickness of 11 ± 2 μm, width of 14 ± 1 cm), and the compaction density is 1.60 g / cm 3, vacuum dried as the negative electrode, lithium metal disc (commercially available, diameter 14mm, thickness 20μm±2) as the counter electrode, the electrolyte is a mixture of 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) (mass ratio 1:1), the separator is PE / PP / PE composite film, and it can be assembled into a button battery.

[0248] (1) First discharge specific capacity and first coulombic efficiency

[0249] Test conditions: the compaction density of the pole piece is 1.65 g / cm 3 The first charge and discharge are performed at a rate of 0.1C, and the charge and discharge are performed at a current density of 0.1C-2C, and the charging voltage is limited to 0.005-2V. The test results of each embodiment and comparative example are shown in Table 2.

[0250] (2) Cycle capacity retention rate

[0251] The compacted density of the pole piece is 1.65g / cm 3 , and the charge and discharge cycles were performed for 200 times at a rate of 0.2C.

[0252] The test results of each embodiment and comparative example are shown in Table 2. In addition, Figure 2 Schematic diagram of the cycle performance of the graphene-coated silicon-tin composite material prepared in Example 1 of the present invention.

[0253] (3) Rate performance

[0254] The compacted density of the pole piece is 1.65g / cm 3 , the charge and discharge cycles were performed for 5 cycles at different rates, and then restored to the initial rate charge and discharge cycle. The test results are shown in Table 3. In addition, Figure 3 Schematic diagram of the rate performance of the graphene-coated silicon-tin composite material prepared in Example 1 of the present invention.

[0255] Table 2

[0256] First discharge capacity at 0.1C mAh / g First coulombic efficiency at 0.1C (%) 200 cycle capacity retention at 0.2C rate (mAh / g) Example 1 2784.7 97.5 2153.1 Example 2 2773.7 96.7 2158.1 Example 3 2780.8 97.9 2160.7 Example 4 2771.5 96.9 2154.6 Example 5 2783.8 97.2 2159.7 Example 6 2773.4 97.3 2159.7 Example 7 2789.2 96.9 2151.1 Example 8 2780.5 97.4 2154.6 Example 9 2772.8 97.1 2152.4 Example 10 2779.6 96.8 2158.1 Embodiment 11 2781.8 97.2 2161.7 Example 12 2784.7 96.9 2155.7 Embodiment 13 2777.7 97.4 2161.4 Embodiment 14 2776.9 96.2 2160.7 Embodiment 15 2778.9 97.1 2159.2 Example 16 2778.4 97.4 2153.8 Embodiment 17 2772.9 96.9 2158.6 Embodiment 18 2772.7 96.6 2160.2 Embodiment 19 2779.6 97.3 2154.7 Embodiment 20 2779.2 96.4 2156.1 Embodiment 21 2781.3 95.9 2135.7 Embodiment 22 2779.5 95.6 2143.6 Embodiment 23 2789.7 95.3 2127.8 Comparative Example 1 4189.5 52.8 2019.5 Comparative Example 2 772.5 69.8 563.8 Comparative Example 3 4031.2 56.9 2054.1 Comparative Example 4 1902.5 93.7 1546.8 Comparative Example 5 2773.5 87.8 2086.9 Comparative Example 6 2896.8 84.9 2124.8 Comparative Example 7 2776.9 94.8 2068.4 Comparative Example 8 2897.3 94.5 2375.7

[0257] Table 3

[0258] 0.1C 0.2C 0.5C 1C 2C 0.1C Example 1 99.20% 98.30% 93.30% 84.40% 74.20% 98.70% Comparative Example 1 89.50% 85.40% 71.20% 56.30% 37.80% 59.70% Comparative Example 2 93.70% 84.30% 73.60% 59.60% 45.70% 88.70% Comparative Example 3 90.50% 87.40% 73.10% 59.30% 42.80% 62.70% Comparative Example 4 98.20% 92.90% 85.30% 69.80% 54.70% 92.80% Comparative Example 5 98.90% 96.70% 89.90% 73.60% 60.80% 95.40% Comparative Example 6 98.60% 94.50% 87.90% 72.60% 59.80% 92.40% Comparative Example 7 99.20% 97.10% 90.60% 80.10% 64.20% 94.70% Comparative Example 8 99.20% 96.90% 90.30% 79.40% 62.50% 95.70%

[0259] Compared with Comparative Examples 1-8, Example 1 has better physical and chemical properties and electrochemical properties. This is because a structure with well-developed three-dimensional pores in the outer layer is constructed by constructing a chestnut-like structure and in-situ growth of graphene. The coordinated effect of the two makes its current density more uniform and the lithium ion transmission rate faster, while simultaneously enhancing the rate performance and ensuring the cycle stability of the silicon-tin composite material.

[0260] Compared with Comparative Example 4, Example 1 has better physical and chemical properties and electrochemical properties. This is because if the amount of humic acid powder added is too high, the silicon content will be reduced, resulting in a lower capacity of the battery; and if the amount of humic acid powder added is too low, it will not be able to play its role. Although the battery capacity is high, the cycle performance and rate are poor.

[0261] Compared with Comparative Example 5, Example 1 has better physical and chemical properties and electrochemical properties. This is because if the polymerization temperature is too low, the phenolic polymerization cannot be completed, and if the temperature is too high, the polymerization process will be accelerated, making it difficult to form a stable polymer.

[0262] Compared with Comparative Examples 3 and 6, Example 1 has better physical and chemical properties and electrochemical properties. This is because the multi-layer carbon coating can alleviate the problem of volume expansion of silicon materials. By co-coating the near silicon-carbon layer with tin and carbon and constructing a chestnut-shaped structure for the far silicon-carbon layer, the lithium ion diffusion rate of the silicon-tin composite material can be enhanced and its rate performance can be improved.

[0263] Compared with Comparative Example 7, Example 1 has better rate performance. This is because the mesoporous structure in the porous tin dioxide can reduce the impact of the low-capacity carbon layer on the material capacity, thereby improving the cycle stability of the silicon material.

[0264] Compared with Comparative Example 8, Example 1 has higher electronic conductivity because the introduction of tin can enhance the diffusion rate of lithium ions in the carbon layer.

[0265] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A silicon-tin composite material, characterized in that: The silicon-tin composite material includes, from the inside to the outside, a core, a first coating layer, and a second coating layer; the core contains silicon material, the first coating layer is a tin-containing carbon layer, and the second coating layer contains a chestnut-shaped carbon layer; the first coating layer contains a first carbon layer, tin dioxide nanoparticles, and a second carbon layer, and the tin nanoparticles are located between the first carbon layer and the second carbon layer.

2. The silicon-tin composite material according to claim 1, characterized in that The silicon-tin composite material further includes a third coating layer, which is a graphene layer, and the third coating layer is coated on the outer surface of the second coating layer.

3. The silicon-tin composite material according to claim 1, characterized in that: The silicon-tin composite material satisfies one or more of the following conditions ae: a. The silicon material is a porous silicon material; b. The silicon material is doped with one or more of boron, phosphorus, nitrogen and sulfur; c. The second coating layer is doped with one or more of nitrogen, boron and phosphorus; d. In terms of mass percentage, the silicon-tin composite material comprises: 54%-61% silicon, 6.0%-7.5% tin, 23%-31% carbon, 0%-1.5% nitrogen, 0%-1% boron, 0.7%-1.2% phosphorus, and 7%-10% oxygen.

4. A method for preparing the silicon-tin composite material according to any one of claims 1 to 3, characterized in that: The preparation method of the silicon-tin composite material comprises the following steps: S1. Coating a tin-containing carbon layer on a silicon material using a solvent gel method, which includes the following steps: S1-1, ultrasonically dispersing a surfactant and tin dioxide in water to form spherical micelles; S1-2, adding a carbon source monomer, a nitrogen source and a catalyst, stirring to obtain a sol; S1-3, adding silicon material to obtain a core-shell colloid; S1-4, heating and polymerization to obtain a gel polymer-coated silicon material; S1-5, carbonizing so that the gel polymer forms a tin-containing carbon layer to obtain a first precursor; S2. Coating the first precursor with a chestnut-shaped carbon layer.

5. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: Step S1 satisfies one or more of the following conditions ae: a. The molar ratio of the surfactant and tin dioxide in step S1-1 is (0.2-0.55): (0.8-1.5); b step S1-1 the surfactant is cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide one or more; c. The molar ratio of the carbon source monomer, nitrogen source and catalyst in step S1-2 to the surfactant in step S1-1 is (1.0-3.0): (0.01-0.09): (0.007-0.03): (0.2-0.55); d. The catalyst in step S1-2 is one or more of sodium carbonate, sodium hydroxide and sodium citrate; e. The molar ratio of the silicon material in step S1-3 to the catalyst in step S1-2 is (1.5-2.5): (0.007-0.03).

6. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: In step S2, the first precursor is coated with a chestnut-shaped carbon layer by a chemical bath deposition method, comprising the following steps: S2-1, ultrasonically dispersing the first precursor in an aqueous solution of a quaternary ammonium salt to obtain a first precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the first precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A; S2-2, heat-treating the composite material A to obtain a composite material B; S2-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source monomer and an initiator, reacting under stirring, centrifuging, washing, and drying to obtain a composite material C; S2-4, calcining the composite material C, and cooling to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer; S2-5. Treat the composite material D with acid to remove the nickel layer, wash, and dry to form a chestnut-shaped carbon layer.

7. The method for preparing the silicon-tin composite material according to claim 6, characterized in that: The step S2 satisfies one or more of the following conditions ag: a. Step S2-1, the mass ratio of the first precursor to the quaternary ammonium salt is (0.1-0.5): (0.009-0.05); b step S2-1 the quaternary ammonium salt is cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide one or more; c. In step S2-1, the mass ratio of the nickel salt, the initiator and the first precursor is (0.1-0.5): (0.02-0.1): (0.1-0.5); d. The nickel salt in step S2-1 is nickel acetate, nickel nitrate or nickel sulfate; e. The mass ratio of the surfactant, carbon source monomer and initiator in step S2-3 is (3-10): (0.1-0.3): (0.2-0.6); f step S2-3 wherein the surfactant is one or more of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecyl sulfonate and sodium α-olefin sulfonate; g. The initiators in steps S2-1 and S2-3 are each independently one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate.

8. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: The product obtained in step S2 is recorded as the second precursor. After step S2, the method further includes: S3, coating the second precursor with a graphene layer, and S3 includes the following steps: S3-1, adding the second precursor and humic acid into water to obtain a premix, and adding an ammonia solution under stirring; The mass ratio of the second precursor to the humic acid is (6-15):1; S3-2, heating, sintering, cooling; S3-3, carbonization, graphene layer is formed in situ after thermal decomposition of humic acid.

9. Use of the silicon-tin composite material according to any one of claims 1 to 3 as an electrode material in a battery.

10. A battery, characterized in that: The battery comprises the silicon-tin composite material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Carbon-coated nano silicon negative electrode material and preparation method thereof

    CN118136819A

Cited By

  • Tin-carbon-coated aluminum-doped positive electrode precursor as well as preparation method and application thereof

    CN120413628A